Mutiply the bracket by -2
(-2)(2y)=-4y
(-2)(-3)= 6
4y^3-4y+6+y
4y^3-4y+y+6 ( combine like terms)
4y^ 3-3y+6
Answer: 4y^ 3-3y+6
Answer:
6/10 or 6/1/10
Step-by-step explanation:
5 3/5 + 1/3 +1/6 =6/10 or 6/1/10
Answer:
They lost 15 games
Step-by-step explanation:
Multiply the percent by the number of games they played to find your answer:
75 x %20
75 x 0.2 = 15
Answer:
x+7
Step-by-step explanation:
So it's been a while since I took Geometry, so I don't know what principle makes these angles equal to each other, but I know that they are in fact equal. So that means that 6x +3 = 45. Subtract 3 from each side gets you 42+6x, then divide each side by 6, which gets you your answer of x=7.
Answer:
6 candy bards
Step-by-step explanation:
$3.12 (total)
each one is $0.52
3.12=0.52b
divide on both sides
3.12/0.52
=6
6 candy bars
(summarized, divide 0.52 by 3.12)